2016
DOI: 10.1111/jzo.12331
|View full text |Cite
|
Sign up to set email alerts
|

Significance of mate selection and adult sex ratio in tiger reintroduction/reinforcement programs

Abstract: Translocations of large carnivores like tiger to restore extirpated populations are increasingly becoming important conservation tools in the face of persistent anthropogenic pressures and relentless habitat loss. Reintroduction success in Panna Tiger Reserve, India was variously attributed to high genetic diversity, less anthropogenic disturbance and stress, efficient execution and technological integrations. Here, we establish parentage relationships and explore the potential of mate choice and appropriate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Another reason for the comparatively larger home range of males in our study area (both reintroduced and historic population) could be because of minimum intra-sex competition (Majumder et al 2012) due to low male tiger density or other unexplained factors. In such situations or when there is large overlap of male home ranges including floater males (Chundawat et al 2016), the population dynamics gets affected, and positively, the females perhaps gain enhanced opportunity to genetic choices for progeny (Reddy et al 2016), which is otherwise limited in large carnivores (Larivière and Ferguson 2003). Male home ranges were larger than those of females, as would be expected in any tiger population and also in other majorly solitary carnivores (Sandell 1989a, b).…”
Section: Discussionmentioning
confidence: 93%
“…Another reason for the comparatively larger home range of males in our study area (both reintroduced and historic population) could be because of minimum intra-sex competition (Majumder et al 2012) due to low male tiger density or other unexplained factors. In such situations or when there is large overlap of male home ranges including floater males (Chundawat et al 2016), the population dynamics gets affected, and positively, the females perhaps gain enhanced opportunity to genetic choices for progeny (Reddy et al 2016), which is otherwise limited in large carnivores (Larivière and Ferguson 2003). Male home ranges were larger than those of females, as would be expected in any tiger population and also in other majorly solitary carnivores (Sandell 1989a, b).…”
Section: Discussionmentioning
confidence: 93%
“…It was found that male tigers in PTR had the largest home range when compared to other Indian reserves. It was also found that the release site had no influence on home range or mate selection (Sarkar et al, 2016), but they tend to avoid mating with genetically close conspecifics (Reddy et al, 2016). The successful tiger reintroduction in PTR has provided scientific and management lessons for planning and up-scaling such recovery efforts in other parts of tiger range countries as well (Gray et al, 2017).…”
Section: Mammalsmentioning
confidence: 99%
“…Finally, for carnivore populations with severely skewed ASR and low abundance, recovery and persistence may well depend on the timely implementation of mitigation measures such as the supplementation of breeding-age individuals to compensate for skewed sex-ratios (Lambertucci et al, 2013;Reddy et al, 2016). With population declines in various areas, this is increasingly being viewed as an essential and viable strategy to achieve tiger population recovery across the species range ( Sankar et al, 2010;Gray et al, 2017;Kolipaka et al, 2017;Harihar et al, 2018), Ecological Process: , and ' 1 Joint posterior distribution: Table 2.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…Dispersal is also typically male-biased: adult females tolerate their female offspring establishing territories in close proximity to their own, but male offspring are driven away. Young males in search of new territories often disperse over large distances and commonly experience aggressive interactions with other males (Reddy et al, 2016;Smith, 1993). Although published information is sparse, ASR (Males:Females) between 1:2 and 1:3 have generally been reported from South Asia (Majumder et al, 2017;Sunquist, 1981).…”
Section: Introductionmentioning
confidence: 99%